Fragment‐Based De Novo Design Reveals a Small‐Molecule Inhibitor of Helicobacter Pylori HtrA1. (9th June 2015) - Perna, Anna M.; Rodrigues, Tiago; Schmidt, Thomas P.; Böhm, Manja; Stutz, Katharina; Reker, Daniel; Pfeiffer, Bernhard; Altmann, Karl‐Heinz; Backert, Steffen; Wessler, Silja; Schneider, Gisbert
Abstract Sustained identification of innovative chemical entities is key for the success of chemical biology and drug discovery. We report the fragment‐based, computer‐assisted de novo design of a small molecule inhibiting Helicobacter pylori HtrA protease. Molecular binding of the designed compound to HtrA was confirmed through biophysical methods, supporting its functional activity in vitro. Hit expansion led to the identification of the currently best‐in‐class HtrA inhibitor. The results obtained reinforce the validity of ligand‐based de novo design and binding‐kinetics‐guided optimization for the efficient discovery of pioneering lead structures and prototyping drug‐like chemical probes with tailored bioactivity.